Requirements for Teacher Capacity and Teacher Training in OECD Countries - Quang Huy, Mai (VNU Journal of Science: Education Research, 2022)
Changes in the socio-economic context and scientific and technological advances since the second half of the 20th century have fundamentally changed the educational context and environment. In that context, there have been many changes in teacher training approaches, models and programs in countries around the world. Following the UNESCO Recommendation (1966) on the Status of Teachers, which considers teaching to be a profession, the movement to professionalizion of teaching and to teacher training has taken place in many countries. Until the beginning of the 21st century, many OECD countries have introduced competency requirements to equip teachers and made changes in teacher training. Based on the literature review, the article analyzes and clarifies requirements for teachers and teacher training in OECD countries